Analisis Ketimpangan Wilayah Pantai Barat dan Pantai Timur Provinsi Sumatera Utara - Aulia, Muhammad; Sirojuzilam, Sirojuzilam; Syafii, M. (Universitas Batanghari Jambi, 2024)
Inequality between regional aspects is common in regional economic activities. This study is to measure the level of regional inequality, the relationship between economic growth, poverty, and the human development index on inequality, and analyze whether there is convergence in the West Coast Region and the East Coast Region of North Sumatra Province. The study uses Williamson index calculations to measure gaps, panel data regression analysis and sigma convergence and beta convergence analysis. The results of the research show that the West Coast Region is indicated by a low level of inequality and the East Coast Region is indicated by a high level of inequality. Economic growth has a positive but not significant impact on inequality in the West Coast Region and a positive and significant impact on inequality in the East Coast Region. Poverty has a positive and significant impact on inequality in the West Coast Region and the East Coast Region. The Human Development Index has a positive and significant impact on inequality in the West Coast Region and the East Coast Region. Simultaneously, Economic Growth, Poverty and the Human Development Index have a positive and significant impact on inequality in the West Coast Region and the East Coast Region. Sigma Convergence does not occur in the West Coast Region but occurs in the East Coast Region. Beta convergence occurs in the West Coast Region and the East Coast Region.